Harnessing the neurotoxic potential of essential oils as biopesticides against stored product pests - Paripoorani, S; Shanthi, M; Murugan, M; Senthil, N; Haripriya, S; Jayakanthan, M; Vijayakumari , N (Plant Science Today, 2025)
The search for sustainable solutions in pest management, particularly for stored-product pests, has accelerated due to growing concerns about food safety, environmental contamination and the development of resistance to synthetic pesticides. Essential oils (EOs), extracted from aromatic plants, possess strong neurotoxic properties and offer ecological safety. These attributes contribute to their significant potential as natural biopesticides. The review highlights current insights into the neurotoxic mechanisms of EOs, particularly their interactions with acetylcholinesterase (AchE), octopaminergic receptors, ion channels and other critical components of insect nervous systems. The efficacy of various EOs against key storage pests such as Sitophilus spp., Tribolium spp. and Callosobruchus spp. is discussed, highlighting their fumigant, contact and repellent activities. Despite their potential, their actual usage is limited due to several issues, including volatility, inconsistent chemical composition and limited residual activity. To address these obstacles, advancements in standardization, molecular understanding and formulation technologies are necessary. The review also emphasizes regulatory challenges and outlines future research directions for integrating EO-based neurotoxic agents into sustainable post-harvest pest management strategies. In conclusion, EOs offer a viable and environmentally sustainable approach to protecting agricultural commodities.